2019
DOI: 10.1002/ece3.5706
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation and nitrogen addition enhance biomass allocation to aboveground in an alpine steppe

Abstract: There are two important allocation hypotheses in plant biomass allocation: allometric and isometric. We tested these two hypotheses in an alpine steppe using plant biomass allocation under nitrogen (N) addition and precipitation (Precip) changes at a community level. An in situ field manipulation experiment was conducted to examine the two hypotheses and the responses of the biomass to N addition (10 g N m−2 y−1) and altered Precip (±50% precipitation) in an alpine steppe on the Qinghai–Tibetan Plateau from 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 42 publications
2
23
0
Order By: Relevance
“…Many studies showed that increased amounts of available N decreased root biomass and R/S 23 . The effect of N on grassland species is determined by rainfall conditions, and increasing soil N availability increased water absorption capacity of plants [23][24][25] . However, little is known with respect to how rainfall changes, N deposition and their interaction in semiarid grasslands will affect the allocation of aboveground and belowground biomass distribution of annuals and perennials.…”
mentioning
confidence: 99%
“…Many studies showed that increased amounts of available N decreased root biomass and R/S 23 . The effect of N on grassland species is determined by rainfall conditions, and increasing soil N availability increased water absorption capacity of plants [23][24][25] . However, little is known with respect to how rainfall changes, N deposition and their interaction in semiarid grasslands will affect the allocation of aboveground and belowground biomass distribution of annuals and perennials.…”
mentioning
confidence: 99%
“…Alpine steppes are the dominant vegetation and comprised Stipa purpurea Grisebach, Poa crymophila Keng, and Leymus secalinus (Georgi) Tzvelev. The soil was classified as calcium soil order, semidry calcium soil suborder, and chestnut soil (Li et al, 2019).…”
Section: Study Site and Experimental Designmentioning
confidence: 99%
“…NH 4 NO 3 was dissolved in 1 L of distilled water and sprinkled evenly twice into the plots of nitrogen addition during the peak growing season (midmonth of June and July). Identical amounts of distilled water were sprayed uniformly on the ambient nitrogen addition plots (Li et al, 2019).…”
Section: Study Site and Experimental Designmentioning
confidence: 99%
“…The responses of grassland ecosystems to N deposition are strongly regulated by precipitation patterns (Harpole et al, 2007). Increased precipitation, particularly under the background of N addition, could increase plant access to soil inorganic N resources (Li et al, 2019), so the effect of N addition on N 2 O emissions may be alleviated by water addition. In addition, decreased precipitation may suppress microbial activity, leading to inefficient N assimilation, despite the presence of large amounts of N substrates in the soil (Homyak et al, 2017;.…”
Section: Discussionmentioning
confidence: 99%